The Assessment of Electrical Energy Management through Case Study in Coal Handling System of Coal-Fired Power Plant - Ari Hastanto; Berkah Fajar Tamtomo Kiono; Jaka Windarta (Universitas Islam Raden Rahmat, Malang, 2024)
Coal Handling System (CHS) is the main system of Coal Fired Power Plant (CFPP), managing coal transportation from Vessel by Ship Unloader to coal yard through belt conveyor (BC) and Stacker/Reclaimer (S/R), then transported to Silo, known as forwarding process. CHS involves various large electric motors. The unwisdom of operating these motors would result in wasteful electrical energy consumption. To assess the energy management, United Nations Industrial Development Organization (UNIDO) provides Energy Management System (EnMS) tools based on ISO 50001 industrial sectors. This tool identifies that operational patterns and maintenance activities have a significant impact on the energy consumption. Technically using Integrated SKF Calculation, applying the scenario of direct replacement conveyor rollers aged more than 2 years by only 30%, saves 103,144.20 kWH per cycle, equal to IDR 102,807,951, rather than replacing rollers when broken only. Meanwhile, Lean Six Sigma concept in increasing cycle performance, could save a monthly 594,984 kWH, equal to IDR 593,044,189.